Mother– and Father–Child Reminiscing About Past Events Involving Pain, Fear, and Sadness: Observational Cohort Study. (21st February 2022) - Pavlova, Maria; Mueri, Kendra; Peterson, PhD, Carole; Graham, PhD, Susan A; Noel, PhD, Melanie
Abstract: Objective: Pain in childhood is prevalent and is associated with fear, particularly in the context of injuries or procedural pain, and negative emotions (e.g., sadness). Pain and fear share a bidirectional relationship, wherein fear exacerbates the experience of pain and pain increases subsequent anticipatory fear. The existing research has focused primarily on children's immediate experience of pain and fear. Research on how children remember or talk about past painful, fearful, or sad events is lacking. Parent–child reminiscing about past pain has been demonstrated to differ from reminiscing about other past negative emotional events (i.e., those involving sadness, but not fear). The present study aimed to examine differences in how parent–child dyads reminisce about past pain, fear, and sadness. Methods: One hundred and three 4-year-old children (55% girls) and their parents (52% fathers) engaged in a narrative elicitation task in which they reminisced about unique past events involving pain, fear, and sadness. Parent–child narratives were coded using established coding schemes based on the developmental psychology literature. Results: Parent–child narratives about pain were characterized by fewer emotion-laden words and explanations, as well as more pain-related words compared to sadness or fearful narratives. Mothers and fathers reminisced with sons and daughters in a similar way across all types of events. Conclusions: Parent–children reminiscing about past painful events differs from reminiscing about other types of distressing events (e.g., involving sadness or fear). This highlights a possibility of differential socialization of pain versus fear. Potential clinical implications of the findings are discussed.